Krypton-85 datasets of the northern and southern hemisphere collected over the past 60 years - Kersting, Arne; Schlosser, Clemens; Schmid, Sabine; Konrad, Martina; Bollhöfer, Andreas; Barry, Karen; Suckow, Axel (Data in Brief, 2020)
With a half-life of 10.7 years, the noble gas radioisotope 85Kr is perfectly suited as a tracer to date ice and water that formed during the past half century. Furthermore, due to its inhomogeneous input into the atmosphere, it is a useful tool to investigate atmospheric circulation and back-trajectory analysis. The data presented here represent a comprehensive time series of atmospheric 85Kr activity concentrations in ground level air that can be used to model northern and southern hemispheric input functions, which is essential to apply 85Kr as a dating tracer. The collection comprises 11 datasets from 4 monitoring stations in the northern and 7 monitoring stations in the southern hemisphere, respectively. In total, it contains about 8000 measurements performed over the past 60 years, making it the largest published 85Kr record.
Gesehen am 29.04.2024